Molecular progression of chronic rhinosinusitis: a pseudotime reconstruction of a transcriptomic dataset - Eggi Erlangga; Ray Soetadji; Rafael Matteo; Ardo Sanjaya (Universa Medicina, 2026)
BackgroundChronic rhinosinusitis (CRS) is a heterogeneous inflammatory disease that is classified based on the presence of nasal polyps. However, whether CRS and nasal polyps represent discrete entities or a continuous progression remains unclear. Most studies have relied on cross-sectional comparisons, which limit insight into its pathophysiology. This study aimed to test whether CRS subtypes lie on a continuous trajectory by applying pseudotime ordering to CRS transcriptomic data. MethodsGene expression data were obtained from the Gene Expression Omnibus (GSE36830), which consists of control, chronic rhinosinusitis without nasal polyps (CRSsNP), uncinate tissue (CRSwNP UT), and nasal polyp tissue (CRSwNP NP) from chronic rhinosinusitis with nasal polyps. Pathway activity was quantified using Gene Set Variation Analysis (GSVA) based on gene sets for immune, inflammatory, and epithelial pathways. Highly variable pathways were selected and used as input to reconstruct a pseudotemporal disease trajectory. Statistical associations were assessed using Spearman correlation and the Jonckheere–Terpstra trend test. ResultsPseudotime reconstruction showed an ordered molecular trajectory extending from control samples through CRSsNP and CRSwNP UT, with nasal polyp samples forming a distinct end stage. Pseudotime showed a strong monotonic association with disease stage (Spearman's ρ=0.743, p<0.001), indicating an ordered progression of molecular changes across disease states. Progressive disease was characterized by increasing activation of immune pathways, including hypersensitivity, alongside declining activity of epithelial stress response and metabolic pathways. ConclusionThese findings demonstrate that CRS represents a continuous molecular disease spectrum. Nasal polyposis emerges as a distinct molecular end state characterized by dominant immune activation. This pseudotime-based framework provides insight into CRS pathogenesis and provides evidence for specific therapeutic strategies.